The Relationship Between Memory Impairment and Health Indicators of the Elderly With Parkinson Disease - Seyede Motahare Hejazi; Hojjat Allah Haghgoo; Ashraf Karbalaei Nouri; Akbar Biglarian; Nazila Akbarfahimi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Parkinson Disease (PD) is a progressive neurodegenerative disorder affecting motor and cognitive functions. Cognitive impairments are related to different causes such as health indicators.   This study aimed to examine the relationship between cognitive impairment and health indicators of patients with PD. Methods & Materials This study was a cross-sectional and descriptive study. By convenience sampling method, a total of 30 PD patients 60-70 years old, diagnosed by a neurologist, were recruited. Cognitive Montreal Test was administrated to measure their global cognitive function. Rey visual test was used to determine their visual memory and the Wechsler test (adult memory) was used to assess their verbal memory. Their sleep quality was assessed by the Pittsburgh Sleep Quality Index. Demographic information and health indicators such as blood pressure were collected via interview. The obtained data were analyzed in SPSS 22. Results The results showed significant relationship between some indicators such as blood pressure with verbal memory (r=-0.514, P=0.004), and sleep disorder (r=-0.421, P=0.031), and visual memory (r=0.368, P=0.045). Conclusion This research revealed that blood pressure and sleep disturbances can affect memory function. Therefore, the cognitive problems in people with PD can be postponed by screening these factors and controlling them with early medical interventions.